Higher Frequency of NK and CD4+ T-Cells in Mucosa and Potent Cytotoxic Response in HIV Controllers (2015)
ABSTARCT: HIV infection induces immune alterations, mainly in gut mucosa, where the main target cells reside. However, the evolution of the infection is variable among infected individuals, as evidenced by HIV controllers who exhibit low or undetectable viral load in the absence of treatment. The aim of this study was to evaluate the frequency, phenotype and activity of T and NK cells in peripheral blood and gut mucosa in a cohort of Colombian HIV controllers. Blood and gut biopsies were included. The frequency and the activation status of T and NK cells were performed by flow cytometry. In addition, Gag-stimulated CD8+ T-cells and cytokine-stimulated NK cells were tested for cytotoxic activity. Finally, microbial translocation was measured by plasma lipopolysaccharide quantification. Compared with HIV-progressors, HIV controllers exhibited higher frequency of CD4+ T and NK cells, and lower expression of activation molecules in blood and mucosal immune cells, as well as lower microbial translocation. An increased production of molecules associated with cytotoxic activity of CD8+ T-cells in blood and mucosa and a higher percentage of polyfunctional CD8+ T cells in blood were also observed in HIV controllers. In addition, an increased activity of NK cells was observed in blood. These findings suggest that HIV controllers have a potent immune response, mainly mediated by cytotoxic cells that control HIV replication, which contribute to reducing alterations at the gut mucosa. Key words: Lipopolysaccharide, Adult CD4-Positive T, Lymphocytes Female, Flow Cytometry